To do or don’t, to take or don’t take: STN-DBS therapy in young PD patient - Şenol, Mehmet Güney; Şimşek, Hakan (Vojnosanitetski pregled, 2021)
Introduction. Parkinson's disease patients with impulse control disorders and dopamine dysregulation syndrome is increasingly recognized. There are reports that such disorders can sometimes be improved by using deep brain stimulation, but sometimes they can get worse. Case report. Our patient was a 30-year-old man with Parkinson's disease since the age of 23. The patient had motor fluctuations on the right with marked bradykinesia, bradymimia and rigidities in the off-periods.  The patient's paraphilia and sexual indiscretions against women were apparent in the on-periods. The patient's eating habits were also changed. The patient underwent subthalamic nucleus-deep brain stimulation (STN-DBS). Significant improvements were seen in the motor and behavior signs of the patient after this procedure had been performed. Conclusion. STN-DBS may be a reasonable option in patients with Parkinson's disease when unwanted dopaminergic side effects occur, and motor disorders and impulse control disorders cannot be improved with drugs.
Keywords: parkinson disease; young adult; subthlamic nucleus; deep brain stimulation; treatment outcome